Bioethics and environmental justice: the case of the presence of pesticides in schoolchildren in rural communities - Muñoz-Quezada, María Teresa; Lucero Mondaca, Boris Andrés (Acta Bioethica, 2019)
A series of studies show the health consequences of people exposed to pesticides either because of their work activity or because they live or study near agricultural land. Occupational exposure to a series of insecticides, herbicides and fungicides is mainly associated with cancer, neurocognitive and motor damage, peripheral polyneuropathy, depression and anxiety, malformations in children at birth, endocrine and reproductive system difficulties, kidney damage and genotoxic effects. Through a review of the literature, the objective of the following article was to elucidate the situation of exposure to pesticides in rural school communities, unveil the bioethical dilemmas in which they are located and the need to apply elements of environmental justice to generate a change and actions to improve their quality of life and health, for the right to live free of environmental pollution. Environmental justice seeks much more than equity and fair treatment and quality similar to that of other non-vulnerable communities, aims to make the same communities demand the need for a more egalitarian society that ensures the right to live in an environment cleansed.